2011
DOI: 10.1038/ismej.2011.173
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community dynamics in the hyporheic zone of an intermittent stream

Abstract: The dynamics of in situ bacterial communities in the hyporheic zone of an intermittent stream were described in high spatiotemporal detail. We assessed community dynamics in stream sediments and interstitial pore water over a two-year period using terminal-restriction fragment length polymorphism. Here, we show that sediments remained saturated despite months of drought and limited hydrologic connectivity. The intermittency of stream surface water affected interstitial pore water communities more than hyporhei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 41 publications
0
54
0
1
Order By: Relevance
“…Several prior studies have demonstrated habitat-driven selection of hyporheic microbial communities, including ones in systems with different hydrology, substratum properties, organic matter inputs, or gradients in heavy-metal contamination (19)(20)(21)(22)(23)(24)(25)(26). Based on this work and recent microbial community assembly studies in the Hanford 300 Area HC (15)(16)(17), deterministic selection imposed by the various DOC sources/ amounts in the three different habitats was expected to lead to distinct microbial assemblages in the colonized sand materials.…”
mentioning
confidence: 69%
“…Several prior studies have demonstrated habitat-driven selection of hyporheic microbial communities, including ones in systems with different hydrology, substratum properties, organic matter inputs, or gradients in heavy-metal contamination (19)(20)(21)(22)(23)(24)(25)(26). Based on this work and recent microbial community assembly studies in the Hanford 300 Area HC (15)(16)(17), deterministic selection imposed by the various DOC sources/ amounts in the three different habitats was expected to lead to distinct microbial assemblages in the colonized sand materials.…”
mentioning
confidence: 69%
“…4) and composition (taxonomical analysis; Table 4) under drought exposure. While modifications in microbial community structure in response to drying events have been reported for temporary streams and wetland sediments (Febria et al, 2012 andFoulquier et al, 2013), the effects of repeated emersion events on the structure of fungal communities associated with leaf substrata remain overlooked (Foulquier et al, 2015). Here, drought stress resulted in a shift that replaced the species A. longissima and C. aquatica by T. marchalianum.…”
Section: Effects Of Individual Stressors On Microbial Leaf Litter Decmentioning
confidence: 92%
“…Since the velocity at which the sediment dries out is difficult to predict, irregular patches are produced according to the prevailing water flow paths or resistance to dry out. Febria et al (2012) showed that surficial microbial communities could remain disconnected from those in the hyporheic, and the drying out of surface water affected interstitial pore water communities to a greater extent than those in the hyporheic sediment. The former showed a transient community, while those inhabiting the hyporheic sediment showed a more permanent composition.…”
Section: Structural Changes and Adaptations Of Biofilms To Dry And Wementioning
confidence: 99%
“…The former showed a transient community, while those inhabiting the hyporheic sediment showed a more permanent composition. Even in these circumstances, bacteria may travel through the pore water and the hyporheic sediments (Febria et al, 2012), showing that these sediments may act as a type of refuge from desiccation for both bacteria and algae.…”
Section: Structural Changes and Adaptations Of Biofilms To Dry And Wementioning
confidence: 99%